Recycling of waste silk fibers towards silk fibroin fibers with different structures through wet spinning technique. (1st November 2019) - Mollahosseini, Hossein; Fashandi, Hossein; Khoddami, Akbar; Zarrebini, Mohammad; Nikukar, Habib
Abstract: This study aims at dealing with a sustainable strategy and cleaner production through recycling of waste silk fibers towards regenerated silk fibroin fibers (RSFFs) with particular and interesting morphologies such as lumen-containing RSFF. This was implemented via wet-spinning of undialyzed solution using two coagulation baths. RSFF structure controlling process was accomplished through adjusting the production parameters. RSFFs with both irregular and circular cross-sections were produced. Coagulation at 23 and 35 °C led to RSFFs with bean- or U-shaped cross-sections. Isolated pores were observed within the cross-section of RSFF coagulated at 35 °C. Further increasing the coagulation bath temperature to 55 °C resulted in lumen-containing RSFF. The RSFFs showed increased wicking properties according to the order of: circular cross-section< bean-shaped cross-section< U-shaped cross-section< lumen-containing cross-section. The messy mass composed of β-cyclodextrin-containing RSFFs showed not only biocompatibility without toxicity, but also significantly enhanced cell proliferation and directed cell growth and adhesion. Graphical abstract: Image 1 Highlights: Production of regenerated silk fibroin fibers (RSFFs) from waste silk fibers. Production of wet-spun RSFFs with different structures using two coagulation baths. Production of lumen-containing RSFFs using a single-orifice spinneret. Developing RSFFs with enhanced wicking properties. Developing RSFFs to suit specific applications requiring directed cell growth.